2022
DOI: 10.5435/jaaos-d-22-00309
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Preoperative 3D Templating in Stemless Anatomic Total Shoulder Arthroplasty

Abstract: Introduction: Recent advances in preoperative 3D templating software allow surgeons to plan implant size and position for stemless total shoulder arthroplasty (TSA). Whether these preoperative plans accurately reflect intraoperative decisions is yet unknown, and the purpose of this study was to evaluate concordance between planned and actual implant sizes in a series of patients undergoing stemless TSA. Methods: A retrospective cohort of consecutive, anatomic, stemless TSA cases performed by two surgeons betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
2
5
1
Order By: Relevance
“…We found that only 61.2% of surgeons’ predictions matched with surgical data, though decision concordance for glenoid-related parameters was significantly higher than for the humeral side. Our findings were considerably lower than previously reported for aTSA [ 10 - 12 , 14 ]. Raiss et al, in a study examining concordance between preoperative planning and implanted glenoid components, reported 85% complete concordance between planned and implanted glenoids [ 10 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We found that only 61.2% of surgeons’ predictions matched with surgical data, though decision concordance for glenoid-related parameters was significantly higher than for the humeral side. Our findings were considerably lower than previously reported for aTSA [ 10 - 12 , 14 ]. Raiss et al, in a study examining concordance between preoperative planning and implanted glenoid components, reported 85% complete concordance between planned and implanted glenoids [ 10 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding glenoid size, 61% were concordant with a plan in our study with all discordant cases within one size. The range of deviation of the discordant glenoid sizes in our study was similar to that of Rechenmacher et al [ 12 ]. Our study differed from that of Raiss et al in that we re-planned our cases at least six months following the actual procedure to minimize the bias inherent in performing the surgery based on adhering to the surgical plan.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations